Influence of cerebral and extracerebral factors on the prognosis of surgical treatment of hemorrhagic stroke - Chepkiy, Leonard; Tsimeyko, Orest; Kamenska, Olga; Moroz, Volodymyr (Ukrainian Neurosurgical Journal, 2012)
Introduction. Hemorrhagic stroke frequency ranges from 10 to 39% in a structure of acute brain vascular diseases. Their treatment is usually conservative. Today surgical treatment is used also. Materials and methods. 221 patients were examined after surgical treatment, 119 of them survived, 102 — died. To estimate patients’ state severity SOFA scale was used. Results. Hemorrhagic stroke in early postoperative period in 54% patients was accompanied by cerebral insufficiency (consciousness impairments according to Glasgow Coma Scale 9 points and less) in 46% — by cerebral dysfunction (Glasgow Coma Scale 10–14 points). At cerebral insufficiency more often lung (in 69%), heart (in 81%) and kidney (in 15%) failure were observed. Frequency of acute cerebral insufficiency is also closely linked with systemic inflammatory response syndrome (SIRS). Expression of heart, lungs and kidneys dysfunction and SIRS criteria (pulse, blood pressure, body temperature, white blood cells quantity) in early postoperative period change parallel with Glasgow Coma Scale parameters. Close correlation was revealed between indicators of multiple organ failure syndrome and SIRS in alive patients, there was no correlation before the lethal outcome. This indicates the decisive role of central nervous system in homeostasis regulation.